WORKPLACE SPIRITUALITY DAN PERFORMA ORGANISASI DI PERGURUAN TINGGI : STUDI ATAS INSTITUT AGAMA ISLAM (IAI) IBRAHIMY GENTENG BANYUWANGI - Afandi, Irfan (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This article aims to examine the relationship between spirituality at work and organizational performance. This study is important to be carried out based on a theory that shows a relationship between the two. The Islamic Institute (IAI) Ibrahimy Genteng is a tertiary institution that develops spirituality to improve organizational performance. This spirituality comes from the leadership of two (2) charismatic kyai namely KHR. As'ad Syamsul Arifin, the caretaker of the Salafiyah-Syafiiyyah Sukorejo Islamic Boarding School and KH. Imam Zarkasyi Djunaidi Caretaker of Pondok Pesantren Bustanul Makmur Genteng Banyuwangi. The spirituality developed at IAI Ibrahimy Genteng is Religious Spirituality. This means that spiritual values ??are developed through religious teachings between istiqomah, sincerity, deliberation and ahlu sunnah wal jamaah. The channel which is used to campaign for religious spirituality through various ways, one of which is through the slayer in the whatsup group. As a result, in the past five years, an increase in organizational performance was marked by a change in status and the addition of study programs in IAI Ibrahimy Genteng Banyuwangi.